Membangun Kreativitas Anak melalui Posko Ramah Anak: Proyek KKN yang Menginspirasi - Ramaita; Alfiza Putri; Cici Safitri; Elhagia Shopiani; Suci Mumtazah Najmi; Roby Anggara (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The Community Service Program (KKN) in Nagari Sumanik, Salimpaung District, Tanah Datar, focused on the Posko Ramah Anak initiative, aimed at developing children's creativity through dance training. The program was conducted by utilizing local resources, such as cloth and bamboo for costumes, and traditional musical instruments from Nagari Sumanik to accompany the dance performances. Despite facing limitations in facilities and equipment, the program has shown significant positive impacts, including increased self-confidence, social skills, and an understanding of local culture among the children. This program uses a participatory approach that encourages creativity, where children are given freedom to create within set boundaries. The program’s success was demonstrated in the dance performances, which were enjoyed and appreciated by the local community. Furthermore, the program successfully introduced local cultural values to the children and the community of Nagari Sumanik, while raising awareness of the importance of art and culture in everyday life. This success provides an example for other community empowerment programs based on art in rural areas, focusing on community empowerment and cultural preservation.